Analysis of formulations containing probiotics accessible to the population of the State of Tabasco - Avila Fernandez, Angela; Cristostomo-Jiménez, Andrea; Morales Contreras, José Antonio; Juarez-Rojop, Isela Esther; Martínez-López, Mirian Carolina (Horizonte Sanitario, 2021)
Objective: In this study, formulations containing probiotics that are sold in establishments in the State of Tabasco were identified, their composition was analyzed and compared with formulations that can be purchased online.Materials and methods: The formulations containing probiotics sold in 21 establishments in the city of Villahermosa were identified and compared with 30 probiotic supplements sold online. Products information was registered in a database and analyzed according to their dosage form, the probiotics genera, species / subspecies that contain and their classification as probiotics or symbiotics and as drugs or supplements.Results: 31 local products and 30 products sold online, formulated with probiotics,  in 6 different dosage forms were analyzed. Only 5 of the local products and none sold online are certified by COFEPRIS as drugs. 48% of the formulations are monostrain and the rest are multistrain. 72% of the formulations are probiotics and the rest are synbiotic. In the 61 products analyzed were identified 46 species belonging to 13 different genera, 39% were common to local and online products. The Lactobacillus and Bifidobacterium genera highlight due to their abundance of species and the number of products that contain them. The genus Bacillus was the only one that was never combined with species of other genera in the formulations.Conclusions: The population of the state of Tabasco can find at least 31 formulations containing probiotics in local establishments. The variety increases if we consider the dietary supplements that can be purchased online. In particular, multistrain supplements. The products certified by COFEPRIS ensure that the benefits of the formulation are supported by clinical trials in humans and are manufactured following the good manufacturing practices.